Drug release behavior of polymeric matrix filled in capsule - Thawatchai Phaechamud; Wanwilai Darunkaisorn (Elsevier, 2016)
A single unit sustainable drug release system was developed using hydroxypropyl methylcellulose (HPMC)-based matrices filled in capsule as the drug delivery device. Release behavior of propranolol HCl from these capsules was investigated and least square fitting was performed for the dissolution data with the different mathematical expressions. Effect of diluent, polymer, pH and hydrodynamic force on the drug release from the developed systems was investigated. The utilization of HPMC as a matrix former extended the drug release longer than 8 h. HPMC viscosity grades affected the drug release, that is, increasing the amount of fillers such as lactose and dibasic calcium phosphate enhanced the drug release rate of HPMC matrices. The hydrodynamic force, type and amount of incorporated polymer apparently influenced the drug release. The physiochemical properties of polymers and interaction between HPMC and other polymers were important factors for prolongation of the drug release. The release mechanism from HPMC-based matrices in capsules was the non-Fickian transport in which the sustainable drug release of HPMC capsules could be achieved by the addition of polymeric matrix.